Family constitution to manage family firms' agency conflicts - Pablo Rodriguez-Garcia; Susana Menéndez Requejo (BRQ Business Research Quarterly, 2023)
This research examines the effectiveness of Family Constitution or Family Protocol agreements in mitigating each type of agency conflict in family firms. We performed a qualitative analysis, through a case study, and found that the succession process is the main driver for implementing this family governance mechanism. Our findings also show that a family constitution is useful in reducing three of the four agency conflicts described in the literature, specifically between family owners and managers, between family shareholders, and with the family at large. Key agreements include training and experience terms for family members to join the firm, transfer clauses of shares inter-vivos and causa mortis, and the development of family governance bodies. However, creditors are generally unaware of the protocol's existence, hindering its potential positive effects, which has important implications for practitioners. Creditors point out its potential usefulness as a hint of orderly and structured continuity of the business.
Keywords: G32; G34; L21; M10; 650; agency theory; case study; family constitution; Family firm; family governance; protocol